(untitled) (Annals of Medical Research, 2024)
Aim: Cytochrome P450 is a hepatic enzyme system responsible for drug metabolism that comprises different iso-enzymes. The CYP2D6 enzyme, which composes 2-4% of all cytochrome enzymes, is responsible for 25% of the metabolisms of the drugs used in clinics. The genetic polymorphisms of this enzyme can change the efficiency and toxicity of the drugs used. In this study, the retrospective evaluation of CYP2D6 gene polymorphisms that influence enzyme activity in the Turkish population is targeted. Materials and Methods: From the 192 patients sent from psychiatry, medical genetics, and neurology polyclinics to our laboratory, we determined CYP2D6 enzyme gene polymorphisms by multiplex polymerase chain reaction (PCR) and multiplex allele-specific primer extension (ASPE). Results: Of all the cases, 82.29% were determined to be extensive, 12.5% intermediate, 2.08% poor, and 3.13% ultra-rapid metabolizers. In our population, the most frequent alleles were *1 (37.63%), *2 (24.75%), *41 (15.15%), *4 (9.85%), and *10 (4.29%), respectively. Conclusion: Compared to previous studies conducted on Turkish society, the percentage of extensive metabolizers was higher in the current examined population. In contrast, the percentages of poor and ultra-rapid metabolizers were lower. In addition, the *41 allele, which has not been studied before in our population, that follows the decrease in enzyme function was detected as the most frequent allele in this study. The fact that the percentage of the cases in which changes were observed was 17.1% will help determine the CYP2D6 gene mutations in the pre-treatment cases.